When close neighbours become good friends: plasticity of behavioural traits in sympatric fishes that form mono- and mixed-species groups. Issue 1 (2nd January 2019) - Middlemiss, Karen L.; Cook, Denham G.; Davison, William
ABSTRACT: Like mono-species fish groups, formation of mixed-species assemblages is likely driven by trophic influences and interspecific behavioural traits. Our aim was to identify how sympatric estuarine species of differing phenotypes form mixed-species group associations, and to identify changes to group structure of fish that migrate between mono- and mixed-species groups. We used sympatric yellow-eyed mullet ( Aldrichetta forsteri ), kahawai ( Arripis trutta ), and Australian snapper ( Chrysophrys auratus ), representing different phenotypes for the mixed-species group, and yellow-eyed mullet for the mono- and mixed-species comparison. Group formation and structure was quantified in predator and foraging treatment groups. We used previous research in mono-species yellow-eyed mullet to compare behavioural plasticity with the current study. Our novel results suggest similar behavioural traits in mono- and mixed-species fish groups have beneficially co-evolved and importantly, behavioural plasticity is necessary for migration between groups. Overall, our observations highlight key behavioural responses associated with mixed-species fish formations in estuarine ecosystems.